Prognostic Significance of Potential Immune Checkpoint Member HHLA2 in Human Tumors: A Comprehensive Analysis - Wang, Ben; Ran, Zhujie; Liu, Mengmeng; Ou, Yunsheng (Frontiers in Immunology, 2019)
Immunological checkpoint inhibitors have been immensely successfully applied in the treatment of cancer, however, a portion of tumor patients can't benefit from checkpoint therapy. The low PD-1/CTLA-4 positive rate and involvement of multiple immunosuppressive pathways are thought to be one of the reasons for treatment failure in non-responding patients. A new immune checkpoint molecule, HHLA2, which was widely expressed in PD-1 negative human tumors, may be a promising target for the improvement of recent immune therapy. Yet, the prognostic value and transcriptional regulatory mechanisms of HHLA2 remains unclear. In this study, we aimed to evaluate the prognostic value and transcriptional regulation mechanism of HHLA2 according to clinical and experimental data from multiple databases, including cBioPortal, TCGA, Cistrome, TIMER, Oncomine, Kaplan-Meier, GeneXplain. It was found that the expression of HHLA2 was significantly elevated in renal tumors, and significantly decreased in colorectal tumors. Pan-cancer survival analysis indicates that HHLA2 was an independent prognostic factor in 9/20 of human cancers. Especially in renal clear cell carcinoma (P = 3.0E-7). Through plotting survival curve in Kaplan-Meier Plotter, it was found that hypomethylation of HHLA2 DNA was a favorable prognostic factor for KIRC patients. Yet, the copy number variant of HHLA2 was not significantly correlated with the overall survival of KIRC patients. Finally, by analyzing the motif of HHLA2 co-expression genes, we identified 15 transcription factors that may be involved in the regulation of the HHLA2 co-expression network. Among these transcription factors, BATF in B lymphocyte and SMAD in monocyte were confirmed to be able to directly bind to HHLA2 DNA according to chip-seq experimental data from Cistrome database.